2020
DOI: 10.1101/2020.04.28.053660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequential screening nominates the Parkinson’s disease associated kinase LRRK2 as a regulator of Clathrin-mediated endocytosis

Abstract: Mutations in leucine-rich repeat kinase 2 (LRRK2) are an established cause of inherited Parkinson's disease (PD). LRRK2 is expressed in both neurons and glia in the central nervous system, but its physiological function(s) in each of these cell types is uncertain. Through sequential screens, we report a functional interaction between LRRK2 and Clathrin adaptor protein complex 2 (AP2). Analysis of LRRK2 KO tissue revealed a significant dysregulation of AP2 complex components, suggesting LRRK2 may act upstream o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 60 publications
(99 reference statements)
0
16
1
Order By: Relevance
“…Thus, the sum of phospho-RAB8 and phospho-RAB10 may be driving the pathogenic LRRK2-mediated vesicular trafficking deficits, and in the future, it will be important to determine the combined levels of both phospho-proteins, and whether LRRK2-mediated endolysosomal trafficking alterations occur in a manner dependent on RAB8A and RAB10 in dopaminergic neurons or other disease-relevant cell types. In addition, endocytic trafficking deficits have also been described for the dopamine D1 receptor and the transferrin receptor [ 62 , 63 ], and it will be interesting to determine whether they are owing to the same LRRK2-mediated inactivation of RAB8A and RAB10 as described here.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, the sum of phospho-RAB8 and phospho-RAB10 may be driving the pathogenic LRRK2-mediated vesicular trafficking deficits, and in the future, it will be important to determine the combined levels of both phospho-proteins, and whether LRRK2-mediated endolysosomal trafficking alterations occur in a manner dependent on RAB8A and RAB10 in dopaminergic neurons or other disease-relevant cell types. In addition, endocytic trafficking deficits have also been described for the dopamine D1 receptor and the transferrin receptor [ 62 , 63 ], and it will be interesting to determine whether they are owing to the same LRRK2-mediated inactivation of RAB8A and RAB10 as described here.…”
Section: Discussionmentioning
confidence: 76%
“…The LRRK2 G2019S mutation can affect Rab8a-mediated receptor recycling and endolysosomal transport (26). Lastly, we have recently shown that LRRK2 mutations can impair clathrin-mediated endocytosis, which governs internalization of different receptors including TfR (38). Therefore, the effect of LRRK2 mutations on TfR recycling may be driven by a Furthermore, iron chelators can rescue dopaminergic neuron loss and behavioral effects caused by intracerebroventricular administration of 6-hydroxydopamine in rats (45).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro evidence suggests that LRRK2 binds or phosphorylates key proteins involved in SV cycle other than Rab5, such as endophilinA, NSF, dynamin, synaptojanin1, auxilin, snapin, synapsin I, AP2 complex, and CaV2.1 channel (Arranz et al., 2015; Bedford et al., 2016; Belluzzi et al., 2016; Heaton et al., 2020; Islam et al., 2016; Matta et al., 2012; Shin et al., 2008; Stafa et al., 2014; Yun et al., 2013). Clearly, LRRK2 is potentially well‐positioned to govern different steps along with both SV endo‐ and exocytosis (see Box 1).…”
Section: Lrrk2 Function At the Pre‐synaptic Sitementioning
confidence: 99%
“…Recent evidence attributes a crucial role to LRRK2 in clathrin‐dependent mechanisms (Heaton et al., 2020). Auxilin, endophilin, and synaptojanin 1 have been proposed as LRRK2 targets and might provide a mechanistic link between LRRK2 and endocytosis.…”
Section: A Model Of Lrrk2 At the Synaptic Sitementioning
confidence: 99%